PENERAPAN MODEL PEMBELAJARAN PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA MATERI POKOK MAKHLUK HIDUP DAN PROSES KEHIDUPAN SEMESTER I KELAS II DI SEKOLAH DASAR NEGERI 3 BESUKI TAHUN PELAJARAN 2012 / 2013 - Mirna Winarni; nur Holifatuz Zahro (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2013)
The aim of this research was to determine the application of the learning outcome Learning Model Picture And Picture improve Learning Outcomes In Subjects Main Material Science of Living Things and Life Processes II Semester Class In School 3 Besuki Primary School Academic Year 2012/2013. Observation and assessment carried out by researchers on learning outcomes of students during the learning activities Picture And Picture experience an increase in learning outcomes. The action is only 44.11% of the 15 students who achieve mastery learning, students who have not completed sailed was about 19 students or 55.89%. In the first cycle, mastery learning students increased to 82.35% or as many as 34 students who completed the classical and the total of 6 students or 17.65% of students who have not completed their study results. Cycle II, students learn mastery increased to 100% of students 34 students who completed the classical style. Mastery learning outcomes of students in science subjects showed greatly improved from before taking action and in doing so the cycle I and II Picture And Picture learning model can be used as a reference to make students active in the classroom and the students do not feel bored in the classroom as well as to improve learning outcomes, especially in science subjects